A Post-colonial Perspective towards Education in Bharat. (December 2014) - Joshi, Ankur; Bindlish, Puneet; Verma, Pawan Kumar
The article explores what could be a post-colonial perspective to the education delivery. If we believe that majority of the problems faced in Bharat have their roots in the colonial residue left in the society post-Independence, we should explore what can be done today. For this exploration was made whether gurukul system of indigenous education can provide the solution to few problems faced by us today? The first person embodied enquiry was made and participant observations were made to understand the pedagogy of gurukul . Hence, the experience of the researchers of the gurukul system of education is presented. Policy relevance is majorly focused on inputs for shaping up education policy with respect to elementary education.